2018
DOI: 10.4047/jap.2018.10.4.259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zirconia surface architecturing technique on the zirconia/veneer interfacial bond strength

Abstract: PURPOSEThe purpose of this study was to evaluate the effect of the zirconia surface architecturing technique (ZSAT) on the bond strength between veneering porcelain and zirconia ceramic.MATERIALS AND METHODS20 sintered zirconia ceramic specimens were used to determine the optimal surface treatment time, and were randomly divided into 4 groups based on treatment times of 0, 1, 2, and 3 hours. After etching with a special solution, the surface was observed under scanning electron microscope, and then the porcela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results of research by Bassir et al [1], Preis et al [6], Yener [18], and Her [24] stated that glazing did not increase the flexural strength, indicating that glazing did not cause changes in the flexural strength of the zirconia samples [3]. The Firing of ceramics after occlusal adjustment also showed the same result did not increase flexural strength [1,26].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of research by Bassir et al [1], Preis et al [6], Yener [18], and Her [24] stated that glazing did not increase the flexural strength, indicating that glazing did not cause changes in the flexural strength of the zirconia samples [3]. The Firing of ceramics after occlusal adjustment also showed the same result did not increase flexural strength [1,26].…”
Section: Discussionmentioning
confidence: 94%
“…Whereas heat treatments conduce a phase change of zirconia from a monoclinic to a tetragonal phase. All treatment procedures can cause stress concentrations on the zirconia surface [19,23,24]. Guazatto et al [25] concluded that an increase in the flexural strength of zirconia was associated with an increase in the number of monoclinic phases after surface treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that zircos-E increased the surface roughness of zirconia, and increased interfacial bond strength between zirconia and veneering porcelain. The optimum etching time was 2 hours [28].…”
Section: Chemical Etchingmentioning
confidence: 99%
“…All-ceramic fixed crown restorations are a popular patient choice due to the aesthetic properties similar to the natural teeth 1. For zirconia, the improved mechanical properties including strength and the physical properties such as its color similar to human teeth make the material more predominant than other ceramics in diverse research fields, in particular, various dental applications 2.…”
Section: Introductionmentioning
confidence: 99%